2013
DOI: 10.1039/c2cc34901a
|View full text |Cite
|
Sign up to set email alerts
|

Does crystal or gel matter to stereochemistry of a reaction? Silver complexation-promoted solid-state [2+2] reaction of an unsymmetrical olefin

Abstract: Head-to-tail and head-to-head [2+2] photodimerization of an unsymmetrical olefin containing benzimidazole and pyridyl groups was achieved by irradiating Ag(I) complexed olefin in crystalline state and gel state, respectively, in stereoselective manner. The [2+2] reaction indicates that the molecular arrangement in a gel is different from that of a xerogel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
(5 reference statements)
3
30
0
Order By: Relevance
“…In a given example the reactions in these three states may have all possible outcomes: 1) all three states may be photochemically reactive or unreactive, 2) all reactive states may form identical or different stereo isomers, 3) it may reactive only in one or two states. Gel state photochemical reactions have been explored recently by several groups utilizing either organic molecules (low molecular weight gelators (LMWGs)), or metal‐ligand self‐assembly (metal‐organic gels (MOGs)) ,…”
Section: Gel State Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a given example the reactions in these three states may have all possible outcomes: 1) all three states may be photochemically reactive or unreactive, 2) all reactive states may form identical or different stereo isomers, 3) it may reactive only in one or two states. Gel state photochemical reactions have been explored recently by several groups utilizing either organic molecules (low molecular weight gelators (LMWGs)), or metal‐ligand self‐assembly (metal‐organic gels (MOGs)) ,…”
Section: Gel State Reactionsmentioning
confidence: 99%
“…These reactions are promoted in solid‐state given the formation of molecular assemblies which increases the proximity of the reacting functional groups. Like crystalline solids, the gels are also composed of supramolecular assemblies with partly restricted movements of molecules that can be used for the promotion of photochemical reactions in stereo selective manner ,. In addition to photochemical [2+2] and [4+4] dimerizations, the polymerization reactions of diacetylenes via 1,4 addition have also been well exploited in the solid state using topochemical principles if the monomer units are aligned properly .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, compared with the well-studied 2-(4-pyridyl)benzimidazole (PyBIm), [10,20] the PyBImE has similar functional segments but larger size, the introducing of the C=C bond can decrease the steric effect of the ligand, thus increasing the coordination ability of N BIm . In the silver complex reported by Biradha et al, the PyBImE ligand acts as didentate ligand, [25] however, the ligand displays unidentate coordination fashion in both complexes 1 and 2 with different N donor atoms, leading to distinct hydrogen bonding systems with uncoordinated N and N-H groups. Complex 3 is a ternary complex, comprised of 2-(2-pyridinium-4-yl-vinyl)benzimidazole cation, BDC 2- teractions aggregate the units into three-dimensional framework.…”
Section: Introductionmentioning
confidence: 98%
“…The ligand L 1 was shown by us earlier to form photoreactive gels and coordination polymer upon reaction with Ag(I). 60 It is interesting to note here that the gel and crystalline CPs resulted in different stereoselective dimers upon irradiation which indicated that the packing of the 1D CPs in gel differs from that of the crystal structure. This is a unique example in which the [2+2] reaction served as a tool to establish the differences between crystalline and gel state molecular aggregations.…”
mentioning
confidence: 95%